2008
DOI: 10.1007/s11746-008-1263-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Occurrence of Steryl Glucosides in Palm and Soy Biodiesel

Abstract: A problem of excessive sedimentation was detected in soy and palm biodiesel, preventing the product from complying with requirements on contamination/ filterability. The objective of the study was to determine the nature of the sediment by different analytical techniques and to obtain data on the typical range of its components in industrially produced biodiesel samples. The sediment was investigated and the appearance of haze is linked to the presence of free steryl glucosides (FSG) above a certain concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 11 publications
3
53
2
3
Order By: Relevance
“…In the paper mentioned above, it was also demonstrated that the higher the refining degree, the lower the impact of SG on finished product, and that the biodiesel prepared from chemically refined oils have less SG problems than the corresponding products obtained by physical processes. Recent papers on this subject have been published by van Hoed et al [9] and Moreau et al [10]. …”
Section: Identification Of Steryl Glucosides -Insoluble Sediment Isolmentioning
confidence: 99%
“…In the paper mentioned above, it was also demonstrated that the higher the refining degree, the lower the impact of SG on finished product, and that the biodiesel prepared from chemically refined oils have less SG problems than the corresponding products obtained by physical processes. Recent papers on this subject have been published by van Hoed et al [9] and Moreau et al [10]. …”
Section: Identification Of Steryl Glucosides -Insoluble Sediment Isolmentioning
confidence: 99%
“…Biodiesel produced from Palm Oilis highly susceptible to form precipitates, formed mainly by sterol glucosides or mixes of Sterol Glucosides and Monoglycerides, which have a negative effect on cold flow properties and are responsible for filter and pipeline plugging (Kochhar, 1983;Moreau, Scott, & Haas, 2008;Ringwald, 2007;Udomsap et al;Van Hoed et al, 2008;Verleyen et al, 2002;Wang, Tang, Salley, & Ng, 2010). The presence of this kind of molecules is quantified through a quality parameter known as Total Contamination (Ministerio de Minas y Energía, 2007;Plata, Gauthier-Maradei, Romero-Bohorquez, Kafarov, & Castillo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 A natureza do precipitado em biodiesel está relacionada ao tipo e pré-tratamento da matéria-prima e à tecnologia de produção do biodiesel. 5,6 Alguns estudos têm-se dedicado à verificação da natureza de resí-duos sólidos em biodiesel, relatando que os compostos identificados como esteróis, esteril-ésteres, esteril-glicosídeos e esteril-glicosídeos esterificados são indutores da formação de precipitados em biodiesel de origem vegetal.…”
Section: Introductionunclassified
“…4 A natureza do precipitado em biodiesel está relacionada ao tipo e pré-tratamento da matéria-prima e à tecnologia de produção do biodiesel. 5,6 Alguns estudos têm-se dedicado à verificação da natureza de resí-duos sólidos em biodiesel, relatando que os compostos identificados como esteróis, esteril-ésteres, esteril-glicosídeos e esteril-glicosídeos esterificados são indutores da formação de precipitados em biodiesel de origem vegetal. 7,8 Esteróis-glicosídeos esterificados estão presentes em óleos vegetais e durante o processo de transesterificação são convertidos em esteril-glicosídeos, os quais levam à formação de materiais sólidos em biodiesel de origem vegetal e em suas misturas com óleo diesel.…”
Section: Introductionunclassified
See 1 more Smart Citation